Effect of Adding Combustion Air on Emission in a Diesel Dual-Fuel Engine with Crude Palm Oil Biodiesel Compressed Natural Gas Fuels - Dori Yuvenda; Bambang Sudarmanta; Arif Wahjudi; Rozy Aini Hirowati (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
A diesel dual-fuel engine uses two fuels designed to reduce the consumption of fossil fuels. Generally, the specific fuel consumption of diesel dual-fuel engines has increased. However, in combination with alternative fuels, namely compressed natural gas injected through air intake, the use of diesel fuel can be reduced. However, using two fuels in a diesel dual-fuel engine increases the equivalent ratio; therefore, the air and fuel mixture becomes richer because the air entering the cylinder during the intake stroke is partially replaced by compressed natural gas. This results in incomplete combustion and increases exhaust emissions, particularly hydrocarbon (HC) and carbon monoxide (CO) emissions. This study aims to improve the combustion process in dual-fuel diesel engines by improving the air-fuel ratio; thus, it can approach the stoichiometric mixture by adding combustion air forcibly to produce complete combustion to reduce CO and HC emissions. An experimental approach using a single-cylinder diesel engine modified into a diesel dual-fuel engine powered by crude palm oil biodiesel and compressed natural gas was adopted. The combustion air was forcibly added to the cylinder using an electric supercharger at different air mass flow rates ranging from 0.007074 to 0.007836 kg/s and different engine loads (1000 to 4000 watts). The results indicated that adding more air to the cylinder could produce complete combustion, reducing the emission levels produced by a diesel dual-fuel engine. An air mass flow rate of 0.007836 kg/s can reduce CO, HC, and particulate matter emissions by averages of 60.55%, 49.63%, and 86.87%, respectively, from the standard diesel dual-fuel engine. Increasing in the amount of oxygen concentration improves the quality of the air-fuel ratio, which results in improved combustion and thereby reducing emissions.